Biopsy-Supported Tumefactive Demyelination of the Central Nervous System in Children. (December 2016) - Hanumanthe, Seema Bangalore; Francisco, Carla; Hart, Janace; Graves, Jennifer; Waubant, Emmanuelle
Pediatric tumefactive lesions remains challenging to clinicians in terms of diagnosis and treatment. The authors describe 11 children with biopsy-proven central nervous system tumefactive demyelination. The mean age of onset was 11 years. Clinical and radiological data coupled with biopsy aided in the diagnosis of tumefactive demyelination. Of the 6 cases in which oligoclonal band data were available, only 3 showed oligoclonal band in the cerebrospinal fluid. Due to poor recovery despite treatment with high-dose glucocorticosteroids, intravenous immunoglobulin, and/or plasmapheresis, 6 cases went on to receive cyclophosphamide with marked improvement. Long-term data were available on 9 cases. Eight of 9 cases were started on preventative multiple sclerosis therapy after initial presentation; 1 is pending discussion with family. Five of the 8 cases had clinical relapse during treatment. Seven cases met 2010 McDonald criteria for multiple sclerosis at follow-up, (1 developed secondary progressive multiple sclerosis), and 2 cases remained as clinically isolated syndrome on treatment.